EFEKTIVITAS SEDUHAN BUNGA ROSELLA TERHADAP KADAR HAEMOGLOBIN PADA IBU HAMIL DI PUSKESMAS SUKAINDAH KABUPATEN BEKASI PERIODE MEI - JUNI TAHUN 2021 - Pratiwi, Arsita (Ikatan Bidan Indonesia (IBI), 2022)
Anemia is one of the factors of maternal death. The government has tried to prevent it by giving Fe tablets during pregnancy. Fe tablets can increase hemoglobin levels, and it is more effective if you consume the Fe tablets by drinking rosella flower steeping. Sukaindah Health Center, Sukakarya District, Bekasi Regency, it was found that the incidence of anemia in pregnant women was quite high. The purpose of the study was to knowing the effectiveness of steeping rosella flowers on increasing hemoglobin levels in pregnant women at the Sukaindah Health Center, Sukakarya District, Bekasi Regency in 2021. Methods: quasi-experimental research using a pre-test-post-test control group design. The sample in this study amounted to 42 respondents with total sampling technique. The data were analyzed using the Independent T-Test. Result: univariate analysis the difference in the average administration of rosella flower steeping and Fe tablets was 0.733 and the difference in the average administration of Fe tablets was 0.262. The results of the bivariate analysis showed the effectiveness of steeping rosella flowers on increasing hemoglobin levels in pregnant women with a significance level of 0.000. The conclusion provision of rosella flower infusion is effective in increasing hemoglobin levels of anemic pregnant women. Suggestions for pregnant women are expected to be diligent in consuming foods that contain iron and be obedient in consuming tablets along with steeping rosella flowers before going to bed in order to increase Hb levels in the mother's blood.